B-Vitamins Influence the Consumption of Macronutrients in Honey Bees - Elsayeh, Walaa Ahmed; Cook, Chelsea; Wright, Geraldine A. (Frontiers in Sustainable Food Systems, 2022)
Insects require dietary sources of B-vitamins, but relatively little is known about whether they regulate B-vitamin intake in the same way they regulate other nutrients. Honey bees meet their B-vitamin requirements mainly from the pollen they collect. Employing the geometric framework for nutrition, we found that honey bees actively regulate their vitamin intake following Bertrand's rule. We fed bees with a diet of essential amino acids (EAAs) and carbohydrate (C) to identify how the addition of B-vitamins affected the regulation of these macronutrients. In our experiments, honey bees preferred vitamins in concentrations comparable to those found in honey bee food (pollen, beebread, and royal jelly). Honey bees actively regulated niacin around an optimal value. Supplementing honey bee diets with B-vitamins influenced the amount of EAAs and carbohydrate ingested differently depending on the type of the vitamin. The impact of these vitamins was observed over the course of seven days where honey bees' mortality increased on diets of low and medium folic acid concentrations. This study provides insights into honey bee food intake regulation and the feeding preferences and sets the basis for future studies considering B-vitamins in honey bees diets.